Fintechs de crédito: uma análise do impacto dessas iniciativas no custo de crédito brasileiro - Rodrigues, Leandro Wolf (Universidade do Vale do Rio dos Sinos, 2021)
Since the middle of the last decade, fintechs have represented a new alternative for financial solutions for Brazilian consumers. Technological advances, added to the increase in connectivity through the spread of smartphones and expansion of internet access, have made access to financial services provided by fintechs favorable. As shown in this study, the Brazilian banking market is oligopolistic. In an oligopoly, increased competition may imply an increase in efficiency, thus reducing extraordinary profits and bringing an increase in economic well-being to society. Thus, this study pursued to analyze whether the arrival of fintechs represents an increase in competition and, consequently, a reduction in the price of financial services for the consumer. The focus of this research was on credit fintechs and their impact on reducing the cost of credit in Brazil. To meet this purpose, this study analyzes the evolution of the total balance disbursed by credit fintechs and the Credit Cost Index released by the Central Bank of Brazil. The balance of credit disbursed by fintechs is still not very representative compared to the volume disbursed by traditional banking institutions, demonstrating how these alternatives are still incipient in the face of this oligopolistic banking market. The present study observed that over the last half of the previous decade the cost of credit in Brazil has reduced, however, this fall is mostly linked to reductions in the cost of funding and a lower default rate. The remuneration of financial institutions for credit operations entered into over the observed period increased, indicating that the effect of the participation of fintechs in credit cannot yet be perceived, as verified the inexpressiveness of the credit balance of fintechs in the total credit of the largest Brazilian banks.
Keywords: Fintechs de crédito; Custo de crédito; Mercado bancário; Concorrência; Credit Fintechs; Credit cost; Banking market; Competition